Analysis of clinical intervention records by pharmacists in an Australian principal referral and specialist women's and newborns' hospital. (24th February 2017) - Teoh, Stephanie W. K.; Hattingh, Laetitia; Lebedevs, Tamara; Parsons, Richard
Abstract: Aim: The objectives of this study were to evaluate clinical interventions recorded by pharmacists in an Australian principal referral and specialist women's and newborns' hospital, as well as to identify common medications involved in each specialty area (neonatology, obstetrics and gynaecology), to assess the risks of medication‐related problems (MRPs) likely to have been prevented, and to obtain institution‐specific MRPs for future staff education. Methods: This retrospective, observational study involved an analysis of all interventions documented by pharmacists from January 2005 to December 2014. The interventions recorded were collated according to ward, medication involved, description of the intervention and the risk classification. Results: There were a total of 14 085 interventions documented over 10 years; 60.33% made in obstetric patients, 28.71% in gynaecology patients and 10.96% in neonates. The three main intervention types were: (i) dose/frequency/time incorrect (25.70%, n = 3260); (ii) prescribing clarification (21.77%, n = 3066); and (iii) medicine omission (15.21%, n = 2143). An average of 12.02% of the interventions were regarded as high‐risk and 0.85% as extreme‐risk. Of the MRPs documented within each specialty, the prevalence of extreme risk interventions was higher in the neonatal ward. Discussion: The most common intervention was identifying incorrect medication dose/frequency/time. Common medications involved in the MRPs included: opioids and antihypertensives in gynaecology; parenteral nutrition and gentamicin in neonatology; and opioids and non‐steroidal anti‐inflammatory drugs (NSAIDs) in obstetrics. The medications involved in high and extreme risk MRPs included gentamicin, opioids and NSAIDs. Conclusion: This study demonstrates that hospital pharmacists contribute to the reduction of MRPs, including some potentially fatal adverse medicine events. These findings also enable targeted, site‐specific education, which is valuable in improving patient safety.